สมบัติทางการไหลและสมบัติทางความร้อนของสตาร์ชจากถั่วเขียว - นภมณี มงคลประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
;This research investigated the rheological and thermal properties of mung bean starch. From chemical analysis, it was found that the mung bean starch contained 10.89% moisture, 0.03% ash, 0.10% protein, 0.31% fat, 0.01% fiber and 88.66% (w/w) carbohydrate. The starch content was 97.98% (w/w) of carbohydrate with 34.49%(w/w) amylose. From Differential Scanning Calorimetry (DSC), it was found that moisture content affected starch gelatinization. At 30% (w/w) moisture content, the endotherm peak was not found which indicated that the water was not sufficient for gelatinization. Increasing moisture content from 40% to 80% (w/w) did not affect the onset temperatures (62.62+-1.45 degree celcius) and peak temperatures (68.42+-0.65 degree celcius). However, the increasing moisture content in the range of 40-80% (w/w) increased the enthalpy of gelatinization (deltaH). It was also found that in moisture range of 50 to 61% (w/w) there were two endotherm peaks overlaping each other, while at the other conditions there was only one peak. Retrogradation of mung bean starch having 70%(w/w) moisture content started within one day, and after three days at -20 degree celcius. From the intrinsic viscosity measurement of mung bean starch pH 3-9 and concentration of NaCl 0-0.2 M, it showed that the intrinsic viscosity did not change indicating the constant starch granule size. The 3-5 g/dl[subscript solvent] mung bean starch paste at pH 7 and 0.1 M NaCl showed to be a pseudoplastic fluid following the Ostwald-De Waele equation : (eta[subscript app] = apparent viscosity in mPa.s, c = starch in g/dl[subscript solv], [gamma = shear rate in sec[superscript -1]). From Creep experiment, Four Element Model as shown below can be used to describe mung bean starch gel having starch concentration of 10.18 g/dl at 27 degree celcius.